C5F10O mixed gas decomposition component adsorption material as well as preparation method and application thereof
By spraying metal organic frame materials on the nanofiber membrane, a metal organic frame/nanofiber composite film was prepared, which solved the problem of insufficient adsorption effect of existing adsorption materials on C3F6 and CF4 of C5F10O mixed gas decomposition components, achieving a more efficient adsorption effect and a lower equipment footprint.
Patent Information
- Application Number
- CN202411780315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing adsorbent materials are insufficient when adsorbing C5F10O mixed gas decomposition components C3F6 and CF4, resulting in a degradation of gas medium insulation performance and increasing the equipment footprint.
Metal organic frame materials (such as HKUST-1(Cu) or HKUST-1(Zn)) are uniformly dispersed on the nanofiber membrane obtained by electrospinning technology by spray doping to prepare a metal organic frame/nanofiber composite membrane to improve adsorption effect.
By increasing the specific surface area and providing more metal active sites, the adsorption effect of C3F6 and CF4 is significantly improved, extending the service life of the adsorbent material, and reducing the equipment footprint.
Smart Images

Figure CN119733484A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorption materials, and specifically relates to a method for adsorbing C5F 10 O adsorption material for the decomposition components of mixed gas hexafluoropropylene and carbon tetrafluoride. Background Art
[0002] Sulfur hexafluoride (SF6) is an insulating gas commonly used in the power industry, with excellent insulation and arc extinguishing properties. But at the same time, SF6 is also a gas with a strong greenhouse effect, and its use is explicitly restricted by the Kyoto Protocol and the Paris Agreement. In order to reduce the power system's dependence on SF6, experts and scholars in the industry have begun to look for new environmentally friendly gases as insulating media for use in power systems. Among them, perfluoropentyl ketone (C5F 10 O) As a new type of environmentally friendly insulating gas, its insulation performance is 1.4 times that of SF6, its chemical properties are stable, its GWP value is about 1, its atmospheric life is only 15 days, and its impact on the environment is far less than SF6.
[0003] In order to meet the different liquefaction temperature requirements in engineering application environments, C5F 10 In actual operation, O is often mixed with CO2. However, under long-term high-voltage operation, discharge or overheating may occur inside the equipment, directly causing C5F 10 O mixed gas decomposes to varying degrees and reacts with trace oxygen and water to form decomposition products such as octafluoropropane (C3F8), carbon tetrafluoride (CF4), hexafluoropropylene (C3F6) and carbonyl fluoride (COF2), resulting in C5F 10 The insulation strength of O gas decreases, which endangers the stability of the power system. If these toxic gases are directly discharged into the atmosphere, they will also pose a threat to human health. Therefore, in order to ensure the long-term operation of the equipment, the C5F 10 The waste gas treatment of the decomposition components of the O mixed gas is crucial.
[0004] At present, the adsorption materials used in the power industry are mainly metal oxides (such as activated alumina), activated carbon (fiber), zeolite / carbon molecular sieve, etc. However, there are a series of problems such as insufficient adsorption effect, resulting in decreased insulation performance of gas dielectrics and increased equipment footprint, which cannot meet the current adsorption requirements of C5F 10 O mixed gas decomposition components C3F6 and CF4 usage requirements. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, one of the purposes of the present invention is to provide a method for 10 O mixed gas decomposition components C3F6 and CF4 have better adsorption effect of adsorption material.
[0006] The second object of the present invention is to provide a C5F 10 Preparation method of adsorbing material for decomposition components of mixed gas.
[0007] The third object of the present invention is to provide a C5F 10 Application of adsorption materials for decomposition components of O mixed gases.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is: a C5F 10 O mixed gas decomposition component adsorption material, the adsorption material is prepared by uniformly dispersing a metal organic framework material on a nanofiber membrane obtained by electrospinning technology through a spray doping method to adsorb C5F 10 Metal-organic framework / nanofiber composite membranes for O mixed gas decomposition components.
[0009] Furthermore, 2.3 to 2.8 mg of the metal organic framework material is sprayed on each square centimeter of the nanofiber membrane.
[0010] Furthermore, the metal organic framework material includes HKUST-1(Cu) or HKUST-1(Zn).
[0011] Furthermore, the nanofiber membrane includes polyacrylonitrile nanofiber membrane, polylactic acid nanofiber membrane, polyvinyl alcohol nanofiber membrane, polyimide nanofiber membrane or polymethyl methacrylate nanofiber membrane.
[0012] A C5F 10 The preparation method of the O mixed gas decomposition component adsorption material comprises the following steps:
[0013] Preparation of nanofiber membrane by electrospinning technology: dissolving a high molecular polymer in an organic solvent, under closed conditions, at a water bath temperature of 50-80°C, stirring continuously for 4-5 hours to obtain an electrospinning precursor solution with a mass percentage concentration of 5-15%; preparing the nanofiber membrane by electrospinning technology;
[0014] Preparation of metal organic framework / nanofiber composite membrane by spray doping method: Mix the metal organic framework material with the organic solvent, stir at room temperature for 0.5 to 1 hour, and then ultrasonically disperse in an ice bath for 2 to 3 hours to obtain a dispersion; load the dispersion into a pneumatic spray gun for spraying, so that the dispersion is evenly sprayed back and forth on the surface of the nanofiber membrane. After spraying, place it in an oven at 80 to 85°C for drying for 12 to 14 hours to obtain a metal organic framework / nanofiber composite membrane.
[0015] Furthermore, in the step of preparing the nanofiber membrane using the electrospinning technology: the polymer includes polyacrylonitrile (PAN), polylactic acid (PLA), polyvinyl alcohol, polyimide or polymethyl methacrylate. The organic solvent is selected from N,N-dimethylformamide (DMF) and chloroform. The conditions of the electrospinning technology are: voltage of 15-25 kV, receiving distance of 15-25 cm, propulsion speed of 1.5-3.5 mL / h, drum speed of 150-200 r / min, temperature of 30-50 ° C, relative humidity of 35-50 RH%, and spinning time of 7-9 h.
[0016] Furthermore, in the preparation of the metal organic framework / nanofiber composite membrane by the spray doping method, the organic solvent is isopropanol. According to the material-liquid ratio, the metal organic framework material: isopropanol = 500mg: 10-15mL. When the dispersion is loaded into the pneumatic spray gun for spraying, the speed of the drum carrying the nanofiber membrane is set to 170-190r / min, and the spraying is repeated at a vertical distance of 5-6cm from the membrane surface and a horizontal range of 10-15cm, so that the metal organic framework material is evenly loaded on the surface of the nanofiber membrane.
[0017] Furthermore, the preparation method of the metal organic framework material includes the following steps: dissolving copper salt or zinc salt in deionized water, dissolving organic ligand in anhydrous ethanol, mixing the two solutions, stirring evenly and transferring them to a polytetrafluoroethylene-lined reactor, hydrothermally reacting at 50 to 80° C. for 10 to 15 hours, cooling to room temperature after the reaction, washing with N,N-dimethylformamide and anhydrous ethanol, centrifuging, and drying to obtain the metal organic framework material.
[0018] Furthermore, the copper salt includes copper chloride, copper nitrate or copper acetate; the zinc salt includes zinc nitrate, zinc chloride or zinc carbonate.
[0019] Furthermore, the organic ligand is trimesic acid.
[0020] The present invention provides a C5F 10 Application of adsorbent material for decomposition components of mixed gas, the adsorbent material is used to adsorb C5F 10 O mixed gas decomposition components.
[0021] Furthermore, the C5F 10 The decomposition components of the O mixed gas include hexafluoropropylene (C3F6) and carbon tetrafluoride (CF4).
[0022] The beneficial effects of the present invention are:
[0023] The adsorption material provided by the present invention cooperates with the metal organic framework material and the porous nanofiber membrane substrate to form a composite membrane with a larger specific surface area and more metal active sites, which promotes the adsorption of gas molecules, thereby accelerating the electron exchange rate between HKUST-1 (Cu) as a sensitive material and gas molecules, and also helps the penetration and diffusion of gas molecules, thereby significantly improving the gas sensitivity and adsorption effect of the adsorption material. In the simulated test of the adsorption material provided by the present invention under the environment of 150kPa and 298k, within a 60-day experimental period, the carbon fluorine product CF4 finally decreased by 153.06ppm compared with the initial concentration, and the concentration of C3F6 was close to 0, which is in line with the C5F 10 There is a demand for better adsorption effect of the decomposition components C3F6 and CF4 of O mixed gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 is a scanning electron microscope image of the HKUST-1(Cu) / PAN composite film prepared in Example 2 of the present invention.
[0026] Figure 2 It is the time-concentration curve of the adsorption of CF4 gas component by the adsorption materials of Examples 2, 3, 4 (A) of the present invention and Comparative Example 1 (B).
[0027] Figure 3 It is the time-concentration curve of the adsorption of C3F6 gas component by the adsorption materials of Examples 2, 3, 4 (A) of the present invention and Comparative Example 1 (B). DETAILED DESCRIPTION
[0028] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In a first aspect of an embodiment of the present invention, a C5F 10 O mixed gas decomposition component adsorption material, the adsorption material is prepared by uniformly dispersing a metal organic framework material on a nanofiber membrane obtained by electrospinning technology through a spray doping method to adsorb C5F10 Metal-organic framework / nanofiber composite membranes for O mixed gas decomposition components.
[0030] The adsorption material provided by the present invention is prepared by electrospinning technology to prepare nanofiber membrane, which is easy to process. Then, the metal organic framework material and the nanofiber membrane porous substrate are coordinated with each other by spray doping method to optimize C5F 10 O mixed gas adsorption material, the formed composite membrane has a larger specific surface area and more metal active sites. Among them, the metal organic framework material is a porous structure with good adsorption performance, and it is interwoven with the porous substrate to have a high specific surface area and a large porosity, which promotes the adsorption of gas molecules and also helps the penetration and diffusion of gas molecules, thereby significantly improving the gas sensitivity and adsorption effect of the adsorption material. In addition, combining the metal organic framework material with the easy-to-process nanofiber membrane can form a specific structure, which is easy to integrate and has excellent processing potential and mechanical properties.
[0031] In some feasible implementations, further, 2.3-2.8 mg of the metal organic framework material is sprayed on each square centimeter of the nanofiber membrane.
[0032] When the amount of metal organic framework material is small, it cannot be evenly distributed on the nanofiber membrane substrate, and the pores between the fibers are not completely filled; when the amount of metal organic framework material is too much, it will cause waste. Therefore, the present invention selects 2.3-2.8 mg of metal organic framework material to be sprayed on each square centimeter of nanofiber membrane, so that the metal organic framework material can be evenly distributed on the nanofiber membrane substrate and fill more than 90% of the pores between the fibers.
[0033] In some feasible embodiments, further, the metal organic framework material includes HKUST-1(Cu) or HKUST-1(Zn).
[0034] The metal organic framework material HKUST-1(Cu) has a porous structure and good adsorption performance. It is interwoven with the porous substrate of the nanofiber membrane and has a high specific surface area and a large porosity. It not only provides more contact sites for HKUST-1(Cu), promotes the adsorption of gas molecules, and thus accelerates the electron exchange rate between HKUST-1(Cu) as a sensitive material and gas molecules, but also helps the penetration and diffusion of gas molecules, thereby significantly improving the gas sensitivity and adsorption effect of the adsorbent material. Through simulation detection, the adsorbent material prepared with HKUST-1(Cu) under the environment of 150kPa and 298k, within a 60-day experimental period, the carbon fluorine product CF4 finally dropped by 153.06ppm compared with the initial concentration, and the concentration of C3F6 was close to 0, which is consistent with the adsorption of C5F 10O mixed gas decomposition components C3F6 and CF4 have a demand for better adsorption effect, therefore, the present invention preferably uses HKUST-1 (Cu) as the metal organic framework material.
[0035] In some feasible embodiments, further, the nanofiber membrane includes polyacrylonitrile nanofiber membrane, polylactic acid nanofiber membrane, polyvinyl alcohol nanofiber membrane, polyimide nanofiber membrane or polymethyl methacrylate nanofiber membrane.
[0036] The polyacrylonitrile nanofiber membrane has good weather resistance and sunlight resistance, can still maintain high strength after being placed outdoors for a long time, and is resistant to chemical reagents, especially inorganic acids and general organic reagents. The polylactic acid nanofiber membrane has excellent biodegradability and biocompatibility, and its high specific surface area and high porosity give it good filtering and separation performance, and can be used in adsorption fields such as water treatment and air purification. Although polymethyl methacrylate nanofiber membrane and polyvinyl alcohol nanofiber membrane have extremely large specific surface area and excellent filtering performance, the preparation conditions are difficult and their performance may need to be further optimized in specific application environments to meet the needs. The polyimide nanofiber membrane has a higher porosity and excellent electrolyte wettability, but the high porosity may cause a decrease in mechanical properties, which causes certain pressure on practical applications. Therefore, the nanofiber membrane of the present invention is preferably polyacrylonitrile nanofiber membrane and polylactic acid nanofiber membrane.
[0037] A second aspect of the embodiment of the present invention provides a C5F 10 The preparation method of the O mixed gas decomposition component adsorption material comprises the following steps:
[0038] Preparation of nanofiber membrane by electrospinning technology: dissolving a high molecular polymer in an organic solvent, under closed conditions, at a water bath temperature of 50-80°C, stirring continuously for 4-5 hours to obtain an electrospinning precursor solution with a mass percentage concentration of 5-15%; preparing the nanofiber membrane by electrospinning technology;
[0039] Preparation of metal organic framework / nanofiber composite membrane by spray doping method: Mix the metal organic framework material with the organic solvent, stir at room temperature for 0.5 to 1 hour, and then ultrasonically disperse in an ice bath for 2 to 3 hours to obtain a dispersion; load the dispersion into a pneumatic spray gun for spraying, so that the dispersion is evenly sprayed back and forth on the surface of the nanofiber membrane. After spraying, place it in an oven at 80 to 85°C for drying for 12 to 14 hours to obtain a metal organic framework / nanofiber composite membrane.
[0040] Electrospinning technology uses the interaction between electrostatic force and surface tension to pull droplets or solutions into fibers under a strong electric field. Through solvent volatilization and solidification, the fibers maintain their shape and structure without damaging the original structure. The present invention prepares nanofiber membranes through electrospinning technology, which has the advantages of wide fiber diameter control range and low cost.
[0041] As an electrospinning precursor solution, when the concentration of the polymer is too low, the spun fibers may be thin and easy to break, with poor strength and toughness, and cannot meet the needs of practical applications. Moreover, during the spinning process, a low-concentration solution may form a beaded structure rather than a continuous fibrous structure due to excessive surface tension. When the concentration of the polymer is too high, its viscosity is too high, resulting in poor solution flow during the spinning process and easy clogging of the nozzle. Due to the high viscosity of the solution, the spinning speed may be slow, and problems such as broken wires may occur, resulting in reduced spinning efficiency. The present invention preferably uses a polymer solution with a mass percentage concentration of 5 to 15% as an electrospinning precursor solution. Within this concentration range, the polymer solution has a high viscosity and appropriate conductivity, which is conducive to forming a stable spinning jet, thereby ensuring the continuity and stability of the spinning process. And at a suitable concentration, the spinning speed is relatively fast, and problems such as clogging the nozzle are not likely to occur, thereby improving the spinning efficiency.
[0042] The present invention prepares the metal organic framework / nanofiber composite membrane by a spray doping method, which has a simple preparation process and can accurately control the amount of metal organic framework material. By spraying, the metal organic framework material can be evenly distributed on the surface of the nanofiber membrane substrate, ensuring the uniformity and consistency of the material.
[0043] In the present invention, the sprayed product is taken off the roller and placed in an oven at 80-85° C. for drying for 12-14 hours, which can not only remove excess solvent but also activate the HKUST-1 (Cu) particle channels.
[0044] In some feasible embodiments, further, in the step of preparing the nanofiber membrane by the electrospinning technology: the high molecular polymer includes polyacrylonitrile (PAN), polylactic acid (PLA), polyvinyl alcohol, polyimide or polymethyl methacrylate. The organic solvent is selected from N,N-dimethylformamide (DMF) and chloroform. The conditions of the electrospinning technology are: voltage of 15-25 kV, receiving distance of 15-25 cm, propulsion speed of 1.5-3.5 mL / h, drum speed of 150-200 r / min, temperature of 30-50 ° C, relative humidity of 35-50 RH%, spinning time of 7-9 h.
[0045] DMF has good solubility for various organic compounds and inorganic compounds and is a non-proton polar solvent. It can be mixed with water and most organic solvents at will, and is particularly suitable for chemical reactions and processes that require high solubility. In the absence of acid, alkali, and water, DMF is relatively stable even if heated to boiling point, showing good chemical stability. Therefore, the preferred organic solvent of the present invention is DMF. The electrostatic spinning conditions proposed by the present invention can not only ensure the stability of the spinning process and the high quality of the fiber, but also improve the spinning efficiency.
[0046] In some feasible embodiments, further, in the preparation of the metal organic framework / nanofiber composite membrane by the spray doping method, the organic solvent is isopropanol. According to the material-liquid ratio, metal organic framework material: isopropanol = 500mg: 10-15mL. When the dispersion is loaded into the pneumatic spray gun for spraying, the speed of the drum carrying the nanofiber membrane is set to 170-190r / min, and the metal organic framework material is evenly loaded on the surface of the nanofiber membrane at a vertical distance of 5-6cm and a horizontal range of 10-15cm.
[0047] If the amount of isopropanol is too low, the reaction efficiency may be reduced; when the amount of isopropanol is too high, isopropanol will form competitive adsorption with the metal organic framework material. Therefore, the present invention preferably, according to the material-liquid ratio, metal organic framework material: isopropanol = 500mg: 10-15mL. The spraying conditions proposed in the present invention can ensure that the coating has a uniform thickness and a smooth surface, thereby improving the overall quality of the coating, improving the adhesion of the coating, and preventing the coating from falling off or cracking.
[0048] In some feasible embodiments, further, the method for preparing the metal organic framework material includes the following steps: dissolving a copper salt or a zinc salt in deionized water, dissolving an organic ligand in anhydrous ethanol, mixing the two solutions, stirring them evenly, and then transferring them to a polytetrafluoroethylene-lined reactor, hydrothermally reacting at 50 to 80° C. for 10 to 15 hours, and after the reaction is completed, cooling to room temperature, washing with N,N-dimethylformamide and anhydrous ethanol, centrifuging, and drying to obtain a metal organic framework material.
[0049] In some feasible embodiments, further, the copper salt includes copper chloride, copper nitrate or copper acetate; the zinc salt includes zinc nitrate, zinc chloride or zinc carbonate. The organic ligand is trimesic acid.
[0050] The advantages of the hydrothermal method include: the hydrothermal method is usually carried out in the medium and low temperature range, and the energy consumption is relatively low, which is conducive to reducing production costs; the reaction is carried out in the liquid phase, so the reaction speed is relatively fast; since the reaction conditions are easy to control, high-efficiency products can be obtained; the process flow of the hydrothermal method is relatively simple and does not require complicated equipment or steps. Therefore, the present invention preferably prepares HKUST-1(Cu) or HKUST-1(Zn) by the hydrothermal method.
[0051] A third aspect of the embodiments of the present invention provides a C5F 10 Application of adsorbent material for decomposition components of mixed gas, the adsorbent material is used to adsorb C5F 10 O mixed gas decomposition components.
[0052] In some feasible embodiments, further, the C5F 10 The decomposition components of the O mixed gas include hexafluoropropylene (C3F6) and carbon tetrafluoride (CF4).
[0053] The adsorption material prepared by the present invention, the metal organic framework material HKUST-1 (Cu) has a porous structure and good adsorption performance, and is interwoven with the porous substrate of the nanofiber membrane to have a high specific surface area and a large porosity, which promotes the adsorption of gas molecules and also helps the penetration and diffusion of gas molecules, thereby significantly improving the gas sensitivity and adsorption effect of the adsorption material. The HKUST-1 (Cu) / PAN composite membrane prepared by the present invention has a strong adsorption capacity for C3F6 and CF4, and can be used as a C5F 10 Through simulation test, the adsorption material prepared by HKUST-1(Cu) in the environment of 150kPa and 298k, within the experimental period of 60 days, the concentration of CF4, a fluorinated product, finally decreased by 153.06ppm compared with the initial concentration, and the concentration of C3F6 was close to 0, which was consistent with the adsorption of C5F 10 There is a demand for better adsorption effect of the decomposition components C3F6 and CF4 of O mixed gas.
[0054] Example 1
[0055] (I) Effect of polymer on the preparation of nanofiber membranes
[0056] Weigh 9g of DMF solvent into a conical flask, add a magnetic stirrer, place it in a 60℃ water bath and stir, then weigh 1g of the polymer powder shown in Table 1 and slowly add it to the stirring conical flask. Cover the bottle cap tightly to prevent water vapor or other impurities from entering the conical flask. Set the water bath temperature to 60℃ and stir continuously for 4h until the solution is clear and transparent to obtain an electrospinning precursor solution with a mass percentage concentration of 10%. Draw 10g of the prepared electrospinning precursor solution into a 20mL syringe, fix the syringe to the spinning machine injection pump, install a 20G needle, and perform electrospinning. The conditions for electrospinning are: voltage of 15 kV, receiving distance between needle and roller of 20 cm, propulsion speed of electrospinning precursor solution of 2.0 mL / h, roller speed of 160 r / min, spinning environment temperature of 35 ° C, relative humidity of 40 RH%, reciprocating platform speed of 900 mm / min, tin foil as receiving substrate, spinning time of 7.5 h, and nanofiber membrane was obtained. The porosity of the obtained nanofiber membrane was tested, and the results are shown in Table 1.
[0057] Table 1
[0058]
[0059]
[0060] The porosity of the nanofiber membrane determines the permeability and filtration efficiency of the membrane. As can be seen from Table 1, the porosity of the nanofiber membrane prepared from high molecular polymers PAN and PLA is relatively high. Therefore, the high molecular polymers of the present invention are preferably polyacrylonitrile (PAN) and polylactic acid (PLA).
[0061] (II) Effect of electrospinning precursor solution concentration on the preparation of nanofiber membranes
[0062] Weigh the DMF solvent in a conical flask, add a magnetic stirrer, place it in a 60°C water bath and stir, then weigh the PAN powder and slowly add it to the stirring conical flask. Cover the bottle cap tightly to prevent water vapor or other impurities from entering the conical flask. Set the water bath temperature to 60°C and stir continuously for 4 hours until the solution is clear and transparent to obtain electrospinning precursor solutions of different concentrations as shown in Table 2. Draw 10g of electrospinning precursor solutions of different concentrations into a 20mL syringe, fix the syringe to the spinning machine injection pump, install a 20G needle, and perform electrospinning. The conditions of electrospinning are as follows: voltage of 15 kV, receiving distance between needle and roller of 20 cm, propulsion speed of electrospinning precursor solution of 2.0 mL / h, roller speed of 160 r / min, spinning environment temperature of 35 °C, relative humidity of 40 RH%, reciprocating platform speed of 900 mm / min, tin foil as receiving substrate, spinning time of 7.5 h, and nanofiber membrane was obtained. The results are shown in Table 2.
[0063] Table 2
[0064] Electrospinning precursor solution concentration Viscosity of electrospinning precursor solution 2% 1.644Pa·s 5% 2.576Pa·s 10% 3.795Pa·s 15% 4.862Pa·s 20% 6.137Pa·s
[0065] If the viscosity of the electrospinning solution is too low, it may be difficult for the spinning solution to form a normal jet, making spinning difficult and ultimately only forming droplets; while if the viscosity is too high, the jet may become more unstable, making spinning difficult to complete, and also easily leading to very uneven diameter and distribution of the obtained nanofibers. As can be seen from Table 2, the viscosity of the electrospinning precursor solution is good when the PAN concentration is between 5% and 15%, while the effect is poor when it is lower than 5% or higher than 15%. Therefore, the present invention preferably has a concentration of 5 to 15% for the electrospinning precursor solution, more preferably 10%.
[0066] Example 2
[0067] A C5F 10 The preparation method of HKUST-1(Cu) / PAN composite membrane, an adsorption material for decomposition components of mixed gas, is as follows:
[0068] 1. Synthesis of HKUST-1(Cu) particles by hydrothermal method
[0069] 1.087g of copper nitrate trihydrate (Cu(NO3)2·3H2O) was dissolved in 15mL of deionized water (DI), and 0.525g of trimesic acid (H3-BTC) was dissolved in 15mL of anhydrous ethanol (C2H6O). The two solutions were mixed, stirred evenly, and then transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction in a 60℃ oven for 12h. After the reaction was completed, the polytetrafluoroethylene liner was removed and cooled to room temperature. The reaction mixture was transferred to a centrifuge tube, and N,N-dimethylformamide (DMF) and anhydrous ethanol were used as detergents for centrifugal washing (9000rpm, 5min). After repeating the washing operation 3 times, the precipitate was placed in an 80℃ oven to dry for 12h to obtain dark blue HKUST-1(Cu) particles.
[0070] 2. Preparation of nanofiber membrane by electrospinning technology
[0071] Use an electronic balance to weigh 9g of DMF solvent into a conical flask, add a magnetic stirrer, place it in a 60℃ water bath and stir, then weigh 1g of PAN powder and slowly add it to the stirring conical flask. Cover the bottle cap tightly to prevent water vapor and other impurities from entering the conical flask. Set the water bath temperature to 60℃ and stir continuously for 4h until the solution is clear and transparent to obtain a PAN electrospinning precursor solution with a mass percentage concentration of 10%. Draw 10g of the prepared PAN electrospinning precursor solution into a 20mL syringe, fix the syringe to the spinning machine injection pump, install a 20G needle, and perform electrospinning. The conditions for electrospinning are as follows: voltage of 15 kV, receiving distance between needle and roller of 20 cm, propulsion speed of electrospinning precursor solution of 2.0 mL / h, roller speed of 160 r / min, spinning environment temperature of 35 °C, relative humidity of 40 RH%, reciprocating platform speed of 900 mm / min, tin foil as receiving substrate, spinning time of 7.5 h, and PAN nanofiber membrane was obtained.
[0072] 3. Preparation of metal organic framework / nanofiber composite membrane by spray doping method
[0073] 500 mg of HKUST-1(Cu) particles were added to a 20 mL sample bottle containing 12 mL of isopropyl alcohol (IPA). After stirring at room temperature for 0.5 h using a magnetic stirrer, an ultrasonic disperser was used to ultrasonically disperse the particles in an ice bath at 750 W for 2 h to obtain a uniform dark blue dispersion. The dispersion was loaded into a pneumatic spray gun for spraying. The speed of the drum carrying the PAN nanofiber membrane was set to 180 r / min. The HKUST-1(Cu) particles were sprayed back and forth at a vertical distance of 5 cm from the membrane surface and within a horizontal range of 10 cm to uniformly load the HKUST-1(Cu) particles on the surface of the PAN nanofiber membrane. After the spraying was completed, the product was removed from the drum and placed in an 80 ° C oven for drying for 12 h to remove excess solvent and activate the HKUST-1(Cu) particle channels to obtain a metal organic framework / nanofiber composite membrane, which was labeled as HKUST-1(Cu) / PAN composite membrane. 2.5 mg of HKUST-1(Cu) was sprayed on each square centimeter of the PAN nanofiber membrane.
[0074] Figure 1 is a scanning electron microscope image of the HKUST-1(Cu) / PAN composite film prepared in this example. Figure 1 It can be seen that the fibers in the composite membrane are interlaced to form a polyacrylonitrile porous substrate. With the polyacrylonitrile porous substrate as a support, HKUST-1(Cu) grows uniformly and stably on the porous substrate.
[0075] Example 3
[0076] A C5F 10The preparation method of HKUST-1(Cu) / PLA composite membrane, an adsorption material for decomposition components of mixed gas, is as follows:
[0077] 1. Synthesis of HKUST-1(Cu) particles by hydrothermal method
[0078] Same as Example 2
[0079] 2. Preparation of nanofiber membrane by electrospinning technology
[0080] Use an electronic balance to weigh 9g of DMF solvent into a conical flask, add a magnetic stirrer, and stir in a 60℃ water bath. Then weigh 2g of PLA powder, dissolve it in 9g of chloroform solution, and then slowly add the dissolved PLA solution to the stirring DMF solvent, and cover the bottle cap to prevent water vapor and other impurities from entering the conical flask. Set the water bath temperature to 60℃ and stir continuously for 4h until the solution is clear and transparent to obtain a PLA electrospinning precursor solution with a mass percentage concentration of 10%. Draw 10g of PLA electrospinning precursor solution into a 20mL syringe, fix the syringe to the injection pump of the spinning machine, install a 20G needle, and perform electrospinning. The conditions for electrospinning are as follows: voltage of 20 kV, receiving distance between needle and roller of 25 cm, propulsion speed of electrospinning precursor solution of 3.0 mL / h, roller speed of 200 r / min, spinning environment temperature of 50 °C, relative humidity of 50 RH%, reciprocating platform speed of 1000 mm / min, tin foil as receiving substrate, spinning time of 9 h, and PLA nanofiber membrane was obtained.
[0081] 3. Preparation of metal organic framework / nanofiber composite membrane by spray doping method
[0082] 500 mg of HKUST-1(Cu) particles were added to a 20 mL sample bottle containing 12 mL of isopropyl alcohol (IPA). After stirring at room temperature for 0.5 h using a magnetic stirrer, an ultrasonic disperser was used to ultrasonically disperse the particles in an ice bath at 750 W for 2 h to obtain a uniform dark blue dispersion. The dispersion was loaded into a pneumatic spray gun for spraying. The speed of the drum loaded with the PLA nanofiber membrane was set to 180 r / min. The HKUST-1(Cu) particles were sprayed back and forth at a vertical distance of 5 cm from the membrane surface and within a horizontal range of 10 cm to uniformly load the HKUST-1(Cu) particles on the surface of the PLA nanofiber membrane. After the spraying was completed, the product was removed from the drum and placed in an 80 ° C oven for drying for 12 h to remove excess solvent and activate the HKUST-1(Cu) particle channels to obtain a metal organic framework / nanofiber composite membrane, which was labeled as HKUST-1(Cu) / PLA composite membrane. 2.5 mg of HKUST-1(Cu) was sprayed on each square centimeter of the PLN nanofiber membrane.
[0083] Example 4
[0084] A C5F 10 The preparation method of HKUST-1(Zn) / PAN composite membrane, an adsorption material for decomposition components of mixed gas, is as follows:
[0085] 1. Synthesis of HKUST-1(Zn) particles by hydrothermal method
[0086] 1.488g zinc nitrate hexahydrate (Zn(NO3)2·6H2O) was dissolved in 15mL deionized water (DI), 0.525g trimesic acid (H3-BTC) was dissolved in 15mL anhydrous ethanol (C2H6O), the two solutions were mixed, stirred evenly and transferred to a polytetrafluoroethylene-lined reactor, and hydrothermally reacted in a 60℃ oven for 15h. After the reaction was completed, the polytetrafluoroethylene liner was removed and cooled to room temperature. The reaction mixture was transferred to a centrifuge tube, and N,N-dimethylformamide (DMF) and anhydrous ethanol were used as detergents for centrifugal washing (9000rpm, 5min). After repeating the washing operation 3 times, the precipitate was placed in a 100℃ oven and dried for 10h to obtain light yellow HKUST-1(Zn) particles.
[0087] 2. Preparation of nanofiber membrane by electrospinning technology
[0088] The same as Example 2, except that the electrospinning conditions were changed, to obtain a PAN nanofiber membrane.
[0089] The conditions for electrospinning are as follows: voltage of 15 kV, receiving distance between needle and roller of 20 cm, propulsion speed of electrospinning precursor solution of 2.0 mL / h, roller speed of 150 r / min, spinning environment temperature of 35 °C, relative humidity of 40 RH%, reciprocating platform speed of 800 mm / min, tin foil as receiving substrate, spinning time of 9 h.
[0090] 3. Preparation of metal organic framework / nanofiber composite membrane by spray doping method
[0091] 500 mg of HKUST-1(Zn) particles were added to a 20 mL sample bottle containing 12 mL of isopropyl alcohol (IPA). After stirring at room temperature for 0.5 h using a magnetic stirrer, an ultrasonic disperser was used to ultrasonically disperse the particles in an ice bath at 750 W for 2 h to obtain a uniform dark blue dispersion. The dispersion was loaded into a pneumatic spray gun for spraying. The speed of the drum carrying the PAN nanofiber membrane was set to 180 r / min. The HKUST-1(Zn) particles were sprayed back and forth at a vertical distance of 5 cm from the membrane surface and within a horizontal range of 10 cm to uniformly load the HKUST-1(Zn) particles on the surface of the PAN nanofiber membrane. After the spraying was completed, the product was removed from the drum and placed in an 80 ° C oven for drying for 12 h to remove excess solvent and activate the HKUST-1(Zn) particle channels to obtain a metal organic framework / nanofiber composite membrane, which was labeled as HKUST-1(Zn) / PAN composite membrane. 2.5 mg of HKUST-1(Zn) was sprayed on each square centimeter of the PAN nanofiber membrane.
[0092] Example 5
[0093] A C5F 10 Application of adsorbent materials for decomposition of mixed gases (I) Effect of different adsorbent materials on C5F 10 Effect of O on adsorption properties of decomposed components of mixed gas
[0094] Here’s how:
[0095] The adsorption materials prepared in Example 2, Example 3 and Example 4 were placed in a stainless steel adsorption chamber at room temperature. The volume of the adsorption chamber was 1.7 L. The adsorption chamber was filled with experimental gas (the experimental gas composition was: 15% C5F 10 O / 85% CO2, the mass is negligible relative to the main gas, where the initial concentration of C3F6 is 545μL / L, and the initial concentration of CF4 is 5μL / L). The experimental gas is filled to 150kPa and allowed to stand at room temperature for adsorption experiments. Gas collection and component detection are performed on the 5th, 10th, 15th, 20th and 60th days respectively. The results are shown in Figure 2 and Figure 3 .
[0096] The adsorption material of Comparative Example 1 is 5A molecular sieve (article number M103775) currently available on the market.
[0097] Figure 2 : is the time-concentration curve of the adsorbent material of Examples 2, 3, 4 and Comparative Example 1 for CF4 gas components. Figure 2 It can be seen that for C5F 10O mixed gas decomposition component carbon tetrafluoride (CF4), within the 60-day experimental period, the concentration of CF4 in the adsorbent prepared in Example 2 continued to decrease, and finally decreased by 153.06ppm compared with the initial concentration. The adsorbent prepared in Example 3 finally decreased by 103.75ppm compared with the initial concentration. The adsorbent prepared in Example 4 finally decreased by 127.21ppm compared with the initial concentration.
[0098] Figure 3 : is the time-concentration curve of the adsorbent materials of Examples 2, 3, 4 and Comparative Example 1 for C3F6 gas components. Figure 3 It can be seen that for C5F 10 O mixed gas decomposition component hexafluoropropylene (C3F6), within the 60-day experimental period, the adsorbent prepared in Example 2, on the 20th day, the C3F6 concentration was close to zero. The adsorbents prepared in Examples 3 and 4 were also able to adsorb it within 60 days, and the C3F6 concentration was close to 0, but the time taken was longer than that in Example 2.
[0099] In summary, the adsorption effect of the adsorption material HKUST-1(Cu) / PAN composite membrane prepared in Example 2 is Figure 2 It can be seen that within 60 days, the concentration of CF4 continued to decrease, and finally decreased by 153.06ppm compared with the initial concentration. Figure 3 It can be seen that the concentration of C3F6 dropped to below 25% on the 5th day, and was close to zero on the 20th day. Combined with the molecular dynamics simulation results, since HKUST-1(Cu) / PAN has a strong interaction with the C=C double bond in C3F6 and the production of C3F6 itself is small, its concentration drops rapidly. The adsorption material of Example 2 has a significant adsorption effect on both C3F6 and CF4 at room temperature, and can meet the requirements of adsorbing C3F6 and CF4, and can be applied to C5F 10 O adsorption material for characteristic decomposition components of mixed gas.
[0100] (II) Effect of metal organic framework loading on C5F 10 Effect of O on adsorption properties of decomposed components of mixed gas
[0101] Here’s how:
[0102] 1. Synthesis of HKUST-1(Cu) particles by hydrothermal method
[0103] The method is the same as in Example 2.
[0104] 2. Preparation of nanofiber membrane by electrospinning technology
[0105] The method is the same as in Example 2.
[0106] 3. Preparation of metal organic framework / nanofiber composite membrane by spray doping method
[0107] The method is the same as that of Example 2. The difference is that the spraying amount of the metal organic framework material is controlled, that is, the metal organic framework material shown in Table 3 is sprayed on each square centimeter of the nanofiber membrane to obtain metal organic framework / nanofiber composite membranes with different spraying amounts.
[0108] 4. Adsorption effect
[0109] The prepared metal organic framework / nanofiber composite membranes with different spraying amounts were placed in a stainless steel adsorption chamber at room temperature. The adsorption chamber volume was 1.7 L. The adsorption chamber was filled with experimental gas (the experimental gas composition was: 15% C5F 10 O / 85% CO2, the mass is negligible relative to the main gas, where the initial concentration of C3F6 is 545μL / L, and the initial concentration of CF4 is 5μL / L), the experimental gas is filled to 150kPa, and the adsorption experiment is performed at room temperature. CF4 gas collection and CF4 component detection are performed once on the 60th day. The results are shown in Table 3.
[0110] Table 3
[0111] Metal-organic framework material content <![CDATA[The final concentration of the CF4 gas component decreased compared to the initial concentration after 60 days]]> <![CDATA[1mg / cm 2 ]]> 77.49ppm <![CDATA[2mg / cm 2 ]]> 121.47ppm <![CDATA[2.3mg / cm 2 ]]> 138.96ppm <![CDATA[2.5mg / cm 2 ]]> 153.06ppm <![CDATA[2.8mg / cm 2 ]]> 155.72ppm <![CDATA[3mg / cm 2 ]]> 152.86ppm <![CDATA[4mg / cm 2 ]]> 136.02ppm
[0112] By spraying different contents of metal organic framework materials, CF4 gas component adsorption experiments were carried out. As shown in Table 3, when the metal organic framework content was low, the CF4 gas adsorption amount was significantly reduced to 2.5 mg / cm 2 When the adsorption capacity is basically saturated, when the metal organic framework content increases, it may cause waste, and even worse, it may cause the fiber pores to be blocked and the adsorption capacity to decrease. In the present invention, it is preferred that 2.3-2.8 mg of metal organic framework material is sprayed on each square centimeter of the nanofiber membrane, and 2.5 mg is more preferred.
[0113] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.
Claims
1. A C5F 10 O mixed gas decomposition component adsorption material, characterized in that, The adsorption material is prepared by uniformly dispersing the metal organic framework material on the nanofiber membrane obtained by electrospinning technology through a spray doping method to adsorb C5F 10 Metal-organic framework / nanofiber composite membranes for O mixed gas decomposition components.
2. A C5F according to claim 1 10 O mixed gas decomposition component adsorption material, characterized in that, 2.3 to 2.8 mg of metal organic framework material is sprayed on each square centimeter of the nanofiber membrane.
3. A C5F according to claim 1 10 O mixed gas decomposition component adsorption material, characterized in that, The metal organic framework material includes HKUST-1 (Cu) or HKUST-1 (Zn); the nanofiber membrane includes polyacrylonitrile nanofiber membrane, polylactic acid nanofiber membrane, polyvinyl alcohol nanofiber membrane, polyimide nanofiber membrane or polymethyl methacrylate nanofiber membrane.
4. A C5F according to any one of claims 1 to 3 10 The preparation method of O mixed gas decomposition component adsorbent material is characterized in that: The steps include: Preparation of nanofiber membrane by electrospinning technology: dissolving a high molecular polymer in an organic solvent, under closed conditions, at a water bath temperature of 50-80°C, stirring continuously for 4-5 hours to obtain an electrospinning precursor solution with a mass percentage concentration of 5-15%; preparing the nanofiber membrane by electrospinning technology; Preparation of metal organic framework / nanofiber composite membrane by spray doping method: Mix the metal organic framework material with the organic solvent, stir at room temperature for 0.5 to 1 hour, and then ultrasonically disperse in an ice bath for 2 to 3 hours to obtain a dispersion; load the dispersion into a pneumatic spray gun for spraying, so that the dispersion is evenly sprayed back and forth on the surface of the nanofiber membrane. After spraying, place it in an oven at 80 to 85°C for drying for 12 to 14 hours to obtain a metal organic framework / nanofiber composite membrane.
5. The preparation method according to claim 4, characterized in that: In the step of preparing nanofiber membrane by electrospinning technology: the high molecular polymer includes polyacrylonitrile, polylactic acid, polyvinyl alcohol, polyimide or polymethyl methacrylate; the organic solvent is selected from N,N-dimethylformamide and chloroform; the conditions of the electrospinning technology are: voltage of 15-25kV, receiving distance of 15-25cm, propulsion speed of 1.5-3.5mL / h, drum speed of 150-200r / min, temperature of 30-50℃, relative humidity of 35-50RH%, and spinning time of 7-9h.
6. The preparation method according to claim 4, characterized in that: In the step of preparing the metal organic framework / nanofiber composite membrane by the spray doping method, the organic solvent is isopropanol; according to the material-liquid ratio, the metal organic framework material: isopropanol = 500 mg: 10-15 mL; when the dispersion is loaded into the pneumatic spray gun for spraying, the rotation speed of the drum carrying the nanofiber membrane is set to 170-190 r / min, and the spraying is repeated at a vertical distance of 5-6 cm from the membrane surface and a horizontal range of 10-15 cm, so that the metal organic framework material is evenly loaded on the surface of the nanofiber membrane.
7. The preparation method according to claim 4, characterized in that: The preparation method of the metal organic framework material comprises the following steps: dissolving a copper salt or a zinc salt in deionized water, dissolving an organic ligand in anhydrous ethanol, mixing the two solutions, stirring them evenly, and then transferring them to a polytetrafluoroethylene lined reactor, performing a hydrothermal reaction at 50 to 80° C. for 10 to 15 hours, cooling to room temperature after the reaction is completed, washing with N,N-dimethylformamide and anhydrous ethanol, centrifuging, and drying to obtain the metal organic framework material.
8. The preparation method according to claim 7, characterized in that: The copper salt includes copper chloride, copper nitrate or copper acetate; the zinc salt includes zinc nitrate, zinc chloride or zinc carbonate; and the organic ligand is trimesic acid.
9. A C5F according to any one of claims 1 to 3 10 Application of O mixed gas decomposition component adsorption material, characterized in that, The adsorption material is used to adsorb C5F 10 O mixed gas decomposition components.
10. The use according to claim 9, characterized in that: The C5F 10 The decomposition components of the O mixed gas include hexafluoropropylene and carbon tetrafluoride.
Citation Information
Patent Citations
Metal organic framework / polymer nanofiber composite membrane material and preparation method thereof
CN107022899A
Metal organic framework-based composite nanofiber membrane as well as preparation method and application thereof
CN113921901A
Method for adsorbing and separating octafluoropropane in sulfur hexafluoride by using metal-organic framework material
CN114471468A
Cited By
Preparation method of hollow fiber membrane separator and method for separating sulfur hexafluoride and nitrogen
CN121016498A
Resistance type gas sensor based on PAN and UiO-66 compounding and preparation and application thereof
CN121476316A
Gas sensitive material based on PVDF / ZIF-8 composite nanofiber membrane as well as preparation method and application of gas sensitive material
CN121653957A
Composite membrane adsorbent material, method for preparing same, and use thereof
CN122499771A